Investigation of the accuracy of the manipulator of the robotic complex constructed on the basis of cycloidal transmission - Strutynskyi, Serhii; Semenchuk, Roman (Technology audit and production reserves, 2021)
The object of research is modern robotic systems used in hotspots. In their arsenal, such mobile works are equipped with manipulators with high-precision hinges, which provide accurate positioning of the gripper (object of manipulation). Considering ground-based robotic complexes with a wheel or caterpillar base, the implementation of the process of manipulation on a stationary basis, a number of problem areas were identified that affect the accuracy of positioning. In the course of research and analysis of modern robotic complexes, their circuit and design of components and mechanisms that provide the necessary qualities and parameters. The problem of developing high-precision hinges is central to the creation of efficient ground-based robotic systems. The methodology of kinematic research of rotary hinges of the manipulator for the ground robotic complex is stated. The analysis of influence of deformations of material of impellers of not involute transfer on accuracy of positioning of a final subject is carried out. A kinetostatic analysis of the manipulator circuit was performed and the maximum moments acting in the hinged units on the drive unit were determined, which allowed to make a quantitative assessment using the Solidworks software package. The mathematical model of construction of transfer and definition of accuracy of a rotary knot for a ground robotic complex, with use of cycloidal transfer without intermediate rolling bodies is investigated and developed. Mathematical modeling and taking into account the features of mechanical processes occurring in the manipulator, allows to increase the technical level of robotic complexes. Ways of improvement are defined for maintenance of a progressive design of the manipulator that not only will satisfy necessary technical characteristics, but also will allow to simplify manufacturing technology. Modern technologies and materials (stereolithography, carbon fiber, superhard materials) make it possible to implement advanced designs of spatial drive systems. Therefore, work in this direction is relevant, as robotic mechanical complexes for special purposes are widely used when performing work in emergencies.